Xylopia aethiopica Fruit Macerate Inhibits Carrageenan-induced Pleurisy in Rats - Gnatoulma Katawa; Fagdéba David Bara; Foulounanna Daria; Pélagie Edlom Tchadie; Tégmaba Gnodja; Kathrin Arndts; Komlan Batawila; Manuel Ritter (Pharmacognosy Research, 2025)
Background: Pleurisy is an inflammatory condition of the pleura that can lead to severe morbidity and mortality. Controlling excessive pleural inflammation is crucial. Xylopia aethiopica, known for its anti-inflammatory properties, may be a potential treatment. Objectives: This study evaluates its immunological mechanisms and toxicological impact. Materials and Methods: Wistar rats were pre-treated with either chloroquine or X. aethiopica fruit macerate before carrageenan-induced pleurisy. Interleukin-6 (IL-6) and Tumor Necrosis Factor-Alpha (TNF-α) levels were measured in blood and pleural exudate via sandwich ELISA. Leukocyte counts were also assessed. Acute and subacute toxicity profiles of the macerate were evaluated in rats. Results: Carrageenan injection induced an inflammatory condition, resulting in increased local and systemic TNF-α and IL-6 levels, with increased leukocyte influx in the pleural cavity. X. aethiopica macerate significantly reduced systemic (p=0.0026) and local (p=0.0004) TNF-α levels, comparable to chloroquine. No acute toxic effects were observed within 48 hours or 14 days. A 28-day oral administration did not induce behavioral changes, and biochemical analyses suggested safety at studied doses. However, histological analyses revealed vascular congestion and inflammation in the liver and kidneys. Conclusion: X. aethiopica macerate exhibits significant anti-inflammatory effects, supporting its potential as a pleurisy treatment. Further research is needed to confirm its clinical applications.
Keywords: anti-inflammatory activity; Pleurisy; Toxicity; Xylopia aethiopica Fruit Macerate